Effectiveness and safety of rivaroxaban and warfarin for prevention of major adverse cardiovascular or limb events in patients with non‐valvular atrial fibrillation and type 2 diabetes. Issue 9 (11th June 2019) - Baker, William L.; Beyer‐Westendorf, Jan; Bunz, Thomas J.; Eriksson, Daniel; Meinecke, Anna‐Katharina; Sood, Nitesh A.; Coleman, Craig I.
Abstract: Aims: To assess the effectiveness and safety of rivaroxaban versus warfarin for the prevention of major adverse cardiovascular events (MACE) and major adverse limb events (MALE) in patients with type 2 diabetes (T2D) and non‐valvular atrial fibrillation (NVAF). Materials and methods: Using MarketScan data from January 2012 to December 2017, we identified oral anticoagulant‐naïve patients with NVAF and comorbid T2D and ≥12 months of insurance coverage prior to rivaroxaban or warfarin initiation. Differences in baseline covariates between cohorts were adjusted for using inverse probability of treatment weights based on propensity scores (absolute standardized differences <0.1 achieved for all covariates after adjustment). Patients were followed until a MACE, MALE or major bleeding event, oral anticoagulant discontinuation/switch, insurance disenrolment or end of data availability. Hazard ratios (HRs) and 95% confidence intervals (CIs) comparing the cohorts were calculated using Cox regression. Results: We identified 10 700 rivaroxaban users (24.1% received a reduced dose) and 13 946 warfarin users. The median (25%, 75% range) age was 70 (62, 79) years, CHA2DS2‐VASc score was 4 (3, 5) and duration of available follow‐up was 1.4 (0.6, 2.7) years. Eleven percent of patients had peripheral artery disease, 5.1% had coronary artery disease, and 5.1% had a prior MALE, at baseline. Rivaroxaban was associated with a 25% (95% CI 4‐41) reduced risk of MACE and a 63% (95% CI 35–79) reduced risk of MALE compared to warfarin. Major bleeding risk did not significantly differ between cohorts (HR 0.95). Conclusions: Among patients with NVAF and T2D treated in routine practice, rivaroxaban was associated with lower risks of both MACE and MALE versus warfarin, with no significant difference in major bleeding.